Prevalência de anodontia entre estudantes do 2O grau da cidade de São José dos Campos-Correlação dessa anomalia entre terceiros molares e outros órgão dentários. - de Melo Castilho, J. C.; Nicodemo, R. A.; Bazzarella, C. B.; de Moraes, L. C. (My University, 1990)
The authors studied 201 school children form both sexes, aging 12 to 14 years, in order to identify anodontia, including in third molars. The results indicated a congenital absence of teeth in 24.37% of the examined children, distributed into 10.44% of boys and 13.93% of girls. Anodontia was observed concerning third molar teeth and other teeth, and the correlation was calculated by the total, sex, and hemiarch. The data were presented and discussed, and the results included several conclusions.
Prevalence of anodontia in 2nd level students in Sao Jose dos Campos-correlation between third molar anomalies and other teeth
Keywords: adolescent; Brazil; child; congenital malformation; female; human; hypodontia; male; molar tooth; sex difference; Adolescent; Anodontia; Child; English Abstract; Female; Human; Male; Molar, Third; Sex Factors